Stereo Educational Game with Vision Based Interaction in Virtual Environment - He, Hanwu; Duan, Xianyin; Wu, Yueming (International Journal of Virtual Reality, 2010)
Interaction and immersion are crucial to educational game quality. Thus, a vision based marker location interaction and stereo rendering method for the game are proposed. This approach could support the players to have more intuitive interaction and more immersion feeling. First, a general architecture of the educational game based on computer vision marker localization interaction was presented. Then, a new method to vision based marker localization and identification interaction was studied. The basic idea of this interaction is using a static camera to track the position and pose information of the marker in the handheld device. So the game system can judge the operation purposes of players such as pick up or put down a virtual objects based on the position and pose information of the marker easily. The experiment result shows this interactive method has a high tracking accuracy. Furthermore, rendering module of the game is designed by using a stereo rendering method, so it can produce stereo vision for players. Last, a feeding animal game for children is realized to verify the presented approaches. Children can carry different food to different animals by a handheld device with marker so that they can learn what food the animals like. The running result illustrates that the presented approaches are effective, and they can provide a natural interaction for game in virtual environment